The effect of ZnO-B₂Oз-SiO₂ (ZBS) glass additives to the microstructure and electrical properties of CaCuзTi4O1₂ (CCTO) electroceramic - Muhammad Qusyairie Saari (2018)
The effect of ZnO-B2O3-SiO2 (ZBS) glass additives to the microstructure and electrical properties of CaCu3Ti4O12 (CCTO) electroceramic has been successfully investigated in this research. CCTO and ZBS glass additives were prepared via solid state reaction and melt quench techniques, respectively. Raw materials of both CCTO and ZBS were wet mixed separately for 24 hours, dried overnight and the CCTO powder was calcined at 900 ˚C for 12 hours using an electrical carbolite furnace. After that, the ZBS powder was melted at 1400 ˚C for 2 hours using an elevator hearth furnace. The ZBS glass was grinded to form fine powder. Different weight percentages (0, 1, 3, 5, 7 and 10 wt%) of ZBS glass powder were added into CCTO (CCTO-ZBS powders), then the powders were wet mixed for 24 hours. The CCTO-ZBS mixtures were dried overnight, compacted at 300 MPa using hydraulic pressure of 6 to 9 mm diameter and 1 to 2 mm thickness (for dielectric properties test) and at 200 MPa of 50 mm diameter and 3 mm thickness (for dielectric breakdown strength test), then sintered at 1040 ˚C for 10 hours using an electrical carbolite furnace. The addition of a small amount of ZBS glass about 1 wt% was able to increase the dielectric constants (33.99%) and reduce the dielectric loss (5.14%) of CCTO measured at 1 MHz. This addition has also increased the relative density to the maximum value (95.90%), helped the formation of single phase of CCTO, increased the grain size (0.35%) and reduced the porosity as compared to pure CCTO. Meanwhile the dielectric breakdown strength (58.0%) and volumetric energy storage density (80.9%) has also improved with 7 wt% of ZBS glass addition.